Do Orthopedic Surgery Residency Program Web Sites Address Diversity and Inclusion?. Issue 2 (May 2022) - Mortman, Ryan J.; Gu, Alex; Berger, Peter; Choudhury, Samrat; Bernstein, Simone A.; Stake, Seth; Fassihi, Safa C.; Thakkar, Savyasachi C.; Campbell, Joshua C.
Background: Orthopedic surgery is one of the least diverse medical specialties. Other medical specialties have employed diversity-related initiatives to increase the number of students underrepresented in medicine (URM). Furthermore, with the suspension of visiting student rotations during the COVID-19 pandemic, medical students used residency program Web sites as a main source of program-specific information. Aims/Purpose: The purpose of this study was to measure the extent to which orthopedic surgery residency program Web sites describe diversity and inclusion initiatives. Methods: The Electronic Residency Application Service (ERAS) was used to identify U.S. orthopedic surgery residency programs. The programs' Web sites were reviewed, and data on commitments to diversity and inclusion were collected. Descriptive statistics of these data were generated. Results: There were 192 residency programs identified and 3 were excluded from the analysis due to lack of Web sites. Of the remaining 189 residency program Web sites, only 55 (29.10%) contained information on diversity and inclusion. Information on a commitment to improving diversity and inclusion was the most prevalent data point found among program Web sites, although it was found on only 15% of program Web sites. Conclusion: Orthopedic surgery residency programs rarely address topics related to diversity and inclusion on their program Web sites. An emphasis on opportunities for URM students and initiatives related to diversity and inclusion on program Web sites may improve URM outreach and serve as one method for increasing URM matriculation into orthopedic surgery.